New Remote Cerebral Microbleeds on T2*-Weighted Echo Planar MRI After Intravenous Thrombolysis for Acute Ischemic Stroke - Jabłoński, Bartosz; Gójska-Grymajło, Anna; Ossowska, Daria; Szurowska, Edyta; Wyszomirski, Adam; Rojek, Bartłomiej; Karaszewski, Bartosz (Frontiers in Neurology, 2022)
Background: The main and well defined complication of intravenous administration of recombinant tissue plasminogen activator (rtPA) in patients with acute ischemic stroke (AIS) is symptomatic intracranial haemorrhage (sICH). However, rtPA might also be connected with formation of cerebral microbleeds (CMBs), located remotely from ischemic lesion, that may remain clinically silent. This association might be important because load of CMBs has been associated with cognitive impairment. We investigated whether administration of rtPA in AIS results in appearance of new CMBs and if the initial load of CMBs is associated with haemorrhagic transformation. Methods: Fifty-nine consecutive patients with AIS treated with rtPA underwent MRI including T2*-Weighted Echo Planar Imaging (T2*-EPI) shortly before and 7-9 days after rtPA administration. We calculated the load of new CMBs located outside the MR diffusion restriction area in the follow-up imaging and assessed hemorrhagic transformation with ECASS-II scoring. Results: Forty-nine patients were included for the final analysis. On initial T2*-EPI- GRE, 37 baseline microbleeds (CMBs) were observed in 14 patients (28.6%). On follow-up T2*-EPI- GRE amount of CMBs increased to a total number of 103. New CMBs were found in 5 (14.3%) of 35 patients without and in 9 (64.3%) of 14 with any baseline CMBs. Multiple logistic regression analysis indicated that presence of baseline CMBs (risk ratio [RR] 5.95, 95% confidence interval [CI] 2.69-13.20, p<0.001) and lower platelets level (risk ratio [RR] 0.992, 95% confidence interval [CI] 0.986-0.998, p=0.007) were independently associated with new CMBs. Baseline load of CMBs was not associated with the risk of haemorrhagic transformation. Conclusion: In this study new CMBs were found in nearly 30% of AIS patients on the 7-9 days after rtPA treatment. Baseline CMBs correlated with higher risk of new CMBs appearing after the rtPA treatment, independently to other factors. At the same time, in our sample, baseline CMBs did not correlate with increased risk of haemorrhagic transformation. Since the associations between the CMBs load and cognitive impairment have already been proved, further studies are warranted to investigate possible associations between thrombolytic treatment of patients with AIS, mainly those with baseline CMBs, and the risk of earlier cognitive decline.